Pelatihan Keuangan dan Pemasaran Untuk Meningkatkan Kapabilitas UMKM Ilham Meubel - Oryza Ardhiarisca; Rahma Rina Wijayanti; Zilvanhisna Emka Fitri; Avisenna Harkat; Muhammad Avan Dwi Adi Nur Kholiq; Muhammad Hanip; Yanuar Ardhika Rahmadhani Ubaidillah (Indonesian Journal Publisher, 2025)
This service activity was carried out at Ilham Meubel Micro, Small and Medium Enterprises (MSMEs) located in Bondowoso. Ilham Meubel is an MSME that operates in the furniture sector. The purpose of carrying out this service is to help Ilham Meubel in solving the problems he faces, namely related to marketing and finance. The marketing carried out by partners so far is still traditional marketing. Meanwhile, in the financial sector, partners have not recorded their finances. The methods of this service activity are field surveys, lectures, broadcasting, practice and discussion. The organizers of the activity consist of four lecturers and three students with expertise in the fields of economics, accounting, management and information technology who are able to solve partner problems in the fields of marketing and finance.This activity lasted for eight months and was divided into three stages, namely survey, preparation for creating Excel-based financial applications and websites and the final stage was training. This service is expected to have a real impact on partners regarding business. management